Extensive Cervical Necrotizing Fasciitis of Odontogenic Origin - Antunes, Antonio Azoubel; Avelar, Rafael Linard; Melo, Willian Morais de [UNESP]; Pereira-Santos, Darklilson; Frota, Riedel (Lippincott Williams & Wilkins, 2013)
Necrotizing fasciitis (NF) is an uncommon infection, but potentially lethal, especially when associated with systemic disorders such as diabetes. The authors report a case of necrotizing fasciitis from odontogenic origin in a patient with uncontrolled diabetes mellitus. The initial diagnosis was based on clinical information, in which multiple necrosis areas in cervical and thoracic regions were observed. Wide antibiotic therapy was applied, followed by surgical drain age and debridement. Culture was positive for methicillin-resistant Staphylococcus aureus. Although the treatment is established, the patient dies after sepsis and failure of vital organs. Clearly, the morbidity associated to this infection, even in diabetic patients, can be minimized if an early diagnosis and effective debridement are done.
Keywords: Dental infection; necrotizing fasciitis; diabetes mellitus; surgical management